2019
DOI: 10.1038/s41588-018-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of up to 1.2 million individuals yield new insights into the genetic etiology of tobacco and alcohol use

Abstract: Tobacco and alcohol use are leading causes of mortality that influence risk for many complex diseases and disorders 1 . They are heritable 2 , 3 and etiologically related 4 , 5 behaviors that have been resistant to gene discovery efforts 6 – 11 . In sample sizes up to 1.2 million individuals, we discovered 566 genetic variants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

74
2,120
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,614 publications
(2,357 citation statements)
references
References 73 publications
74
2,120
7
2
Order By: Relevance
“…Young adulthood is also a period when romantic partnerships become increasing salient, as young adults in committed relationships consume less alcohol than their single peers . We used results from the largest mega‐analysis to date on alcohol consumption , which used drinks per week in ~1 million individuals, to calculate genome‐wide polygenic scores in our independent, population‐based sample. We tested: (1) whether these polygenic risk scores were associated with alcohol use, heavy consumption and alcohol problems; (2) whether being in a romantic relationship changed the association between genetic risk and alcohol outcomes; and (3) because there are sex differences in patterns of alcohol use and in the prevalence of alcohol use disorders and heavy consumption and the fact that social control processes may operate differently for men and women in the context of relationships , we examined whether there were sex differences in G × E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young adulthood is also a period when romantic partnerships become increasing salient, as young adults in committed relationships consume less alcohol than their single peers . We used results from the largest mega‐analysis to date on alcohol consumption , which used drinks per week in ~1 million individuals, to calculate genome‐wide polygenic scores in our independent, population‐based sample. We tested: (1) whether these polygenic risk scores were associated with alcohol use, heavy consumption and alcohol problems; (2) whether being in a romantic relationship changed the association between genetic risk and alcohol outcomes; and (3) because there are sex differences in patterns of alcohol use and in the prevalence of alcohol use disorders and heavy consumption and the fact that social control processes may operate differently for men and women in the context of relationships , we examined whether there were sex differences in G × E .…”
Section: Introductionmentioning
confidence: 99%
“…Young adulthood is also a period when romantic partnerships become increasing salient, as young adults in committed relationships consume less alcohol than their single peers [39]. We used results from the largest mega-analysis to date on alcohol consumption [15], which used drinks per week in~1 million individuals, to calculate genome-wide polygenic scores in our independent, population-based sample. We tested: (1) whether these polygenic risk scores were associated with alcohol use, heavy consumption and alcohol problems;…”
Section: Introductionmentioning
confidence: 99%
“…First, a weighted median MR was performed, which allows for 50% of the instrumental variables to be invalid. 30 Second, MR-Egger regression was performed, which allows all the instrumental variables to be subject to direct effects (i.e., horizontal pleiotropy), 31 22 we excluded SNPs (Supplementary Table 1) that were associated with any smoking phenotype at genome-wide significance (P < 5e-8; n = 3) and suggestive significance (P < 5e-6; n = 7) as a sensitivity analysis.…”
Section: Mendelian Randomization Analysismentioning
confidence: 99%
“…Numerous twin, adoption and family studies have established the important role of genetics in AUDs, with heritabilities estimated between 49 and 60% . Recent large‐scale human genome‐wide association studies (GWAS) have identified various loci associated with alcohol behaviors . In addition to the widely‐replicated associations with genes encoding alcohol‐metabolizing enzymes, neuronal genes such as SLC39A8 and DRD2 also emerged as significant hits .…”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%
“…[89][90][91][92] Recent large-scale human genome-wide association studies (GWAS) have identified various loci associated with alcohol behaviors. 81,93,94 In addition to the widely-replicated associations with genes encoding alcohol-metabolizing enzymes, neuronal genes such as SLC39A8 and DRD2 also emerged as significant hits. 81 For exercise, twin studies investigating leisure-time physical activity (LTPA), physical activity (PA), physical inactivity (PI) and sedentary behaviors have yielded heritability estimates ranging from~25 to 85% in humans.…”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%